2019
DOI: 10.1016/j.jeconom.2019.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Robust inference for threshold regression models

Abstract: This paper is concerned with inference in threshold regression models when the practitioners do not know whether at the threshold point the true specification has a kink or a jump. We nest previous works that assume either continuity or discontinuity at the threshold point and develop robust inference methods on the parameters of the model, which are valid under both specifications. In particular, we found that the parameter values under the kink restriction are irregular points of the Hessian matrix of the ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 34 publications
0
39
0
Order By: Relevance
“…Even when the true model is a kink model, it is shown that the asymptotic distribution of the GMM estimator in the preceding section is valid. This contrasts with the least-squares estimator for the linear regression, for which Hidalgo, Lee, and Seo (2019) have shown that the cube root phenomenon appears.…”
Section: Modelmentioning
confidence: 80%
“…Even when the true model is a kink model, it is shown that the asymptotic distribution of the GMM estimator in the preceding section is valid. This contrasts with the least-squares estimator for the linear regression, for which Hidalgo, Lee, and Seo (2019) have shown that the cube root phenomenon appears.…”
Section: Modelmentioning
confidence: 80%
“…The estimator's convergence rate was further improved to within a logarithmic factor of O p (n −1/2 ) in Baranowski et al (2019) under more restrictive assumptions. See also Hansen (2017) for inference in the presence of a kink, Hidalgo et al (2019) for a test of continuity at the breakpoint, and an as yet unpublished 2017 paper by Y. Dong from the University of California Irvine for a related problem on treatment effect evaluation. There has also been work on kink location estimation in various univariate nonparametric regression settings.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, the study examines the presence of kinks in the models. The paper discovers that asides from the thresholds, there are kinks in the models (Hansen, 2017; Hidalgo, Lee, & Seo, 2019).…”
Section: Empirical Results and Discussionmentioning
confidence: 99%